Empathize with your audience to share your story. Issue 10 (June 2018) - Hope, Joan
Abstract : Hosting the television show Scientific American Frontiers made it clear to Alan Alda that many scientists aren't very good at communicating. In an effort to address that problem, Alda launched the Alan Alda Center for Communicating Science at Stony Brook University. He also wrote the book If I Understood You, Would I Have This Look on My Face? My Adventures in the Art and Science of Relating and Communicating .